(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
A simple reverse-phase high-performance liquid chromatographic method has been developed for the determination of morphine in human urine using codeine as internal standard. After solid-phase extraction (SPE), the compounds were separated on a reversed-phase Acentis Express C18 column (150mm × 4.6mm, 2.7µm) equipped with a guard column (2.7 µm, 5 mm × 4.6 mm). The channel on the UV detector was configured to acquire data at 285 nm. The mobile phase was composed of acetonitrile-sodium acetate (pH 4; 0.01M) (10:90, v/v). The flow rate was 0.6 ml/min. Injection volume was 30 ml. The run time was set at 10 min. The retention time for morphine and codeine were approximately 3.4 min and 7.2 min, respectively. The calibration curve was linear over the concentration range of 150-2000 ng/ml with good linearity. Limit of detection (LOD) and quantification (LOQ) in urine were 50 and 150 ng/ml, respectively. Recovery was greater than 85%. The inter-day precision was from 9.27% to 12.53% and the intra-day precision ranged from 1.63% to 4.58%. The inter-day accuracy ranged 81.45% to 109.88% and intra-day accuracy ranged from 81.56% to 106.69%. The stability studies showed that morphine was stable up to one month in urine. This method was applied to determine morphine concentration in human urine for toxicology analysis.